Gambaran Waktu Penyediaan Dokumen Rekam Medis di Puskesmas Karang Pule Kota Mataram - Maria Yovita; Uswatun Hasanah; Reni Chairunnisah (Jurnal Rekam Medis dan Informasi Kesehatan, 2019)
The time for the provision of medical record documents from when the patient registers until the medical record documents are provided or found by officers with a minimum standard of service is 10 minutes. The purpose of this study was to determine the time description of the supply of medical record documents at the Karang Pule Health Center in Mataram City. The research design used is descriptive. The population in this study was 200 medical record documents with a total sample of 67 documents. The sampling technique used is accidental sampling. The results showed that the frequency distribution of old patient medical record documents 65 and new patient medical record documents 2. The average time needed to provide medical records for old patients is 1 minute 29 seconds and new patients 2 minutes 29 seconds. The average length of time for providing medical records in TPP is 51.65 seconds, Filling 17.64 seconds, 32 seconds distribution. Based on these results it can be concluded that when providing medical record documents at the Karang Pule Puskesmas it has met the minimum service standards, it is recommended to the Karang Pule Puskesmas to maintain and improve service quality.